Implementation of Educational Administration Theory to Improve the Performance of Madrasah Ibtidaiyah - Shintya Rahma Fatunnisa; Dien Majid Ikhwan; M. Abdillah Subhin (Jurnal Pendidikan Nusantara, 2026)
This study aims to examine the implementation of educational administration concepts and theories in efforts to improve the performance of the educational institution at MIM 1 Simo Jenangan, Ponorogo Regency, as well as to analyze the extent to which their application contributes to improving institutional performance. The study employs a descriptive qualitative approach, with data collection techniques including observation, in-depth interviews, and documentation. Data were analyzed using an interactive analysis model comprising data reduction, data presentation, and drawing conclusions, with data validity tested through triangulation of sources and methods. The results indicate that the concepts and theories of educational administration were applied in a structured and consistent manner across the functions of planning, organizing, implementing, controlling and evaluating. This application has led to improved quality of educational services, optimized management of human and non-human resources, and increased stakeholder satisfaction (students, teachers, parents, and the community). It can be concluded that sound educational administration plays a crucial role in promoting the effectiveness and progress of educational institutions. The consistent application of educational administration theory not only supports operational efficiency but also fosters improvements in the quality of learning and the sustainable development of the institution.